2018
DOI: 10.3892/or.2018.6231
|View full text |Cite|
|
Sign up to set email alerts
|

FNDC3B promotes epithelial-mesenchymal transition in tongue squamous cell carcinoma cells in a hypoxic microenvironment

Abstract: The primary reasons for the treatment failure of patients with oral tongue squamous cell carcinoma (OTSCC) are metastasis and tumor recurrence. Identifying the exact mechanisms underlying metastasis is a key point in improving patient prognosis. It has been reported that a hypoxic microenvironment plays an important role during the metastasis of malignancies. We found that the expression of fibronectin type III domain containing 3B (FNDC3B) is positively correlated with lymph node metastasis and advanced cTNM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…FNDC3B , also known as FAD104 (factor for adipocyte differentiation 104), is located at 3q26, and is amplified in more than 20% of human tumors 24,25 . Recently, FNDC3B was found to serve as an oncogene and it can promote tumorigenesis and metastasis in various cancer types 24‐28 . FNDC3B can promote cell migration and metastasis by cooperating with annexin A2 (ANXA2) in hepatocellular carcinoma 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FNDC3B , also known as FAD104 (factor for adipocyte differentiation 104), is located at 3q26, and is amplified in more than 20% of human tumors 24,25 . Recently, FNDC3B was found to serve as an oncogene and it can promote tumorigenesis and metastasis in various cancer types 24‐28 . FNDC3B can promote cell migration and metastasis by cooperating with annexin A2 (ANXA2) in hepatocellular carcinoma 26 .…”
Section: Discussionmentioning
confidence: 99%
“…FNDC3B is correlated with poor survival and can promote epithelial‐mesenchymal transition in lung adenocarcinoma 27 . FNDC3B can promote migration and invasion in tongue squamous cell carcinoma 28 . In addition, Fan et al found that there was a binding site for miR‐143 in the 3′‐UTR region of FNDC3B , which was involved in the regulation of prostate cancer metastasis 29 .…”
Section: Discussionmentioning
confidence: 99%
“…FNDC3B is mainly composed of fibronectin III (FNIII) domain [27], which has been widely reported to be upregulated in cancer as a oncogene [28], such as hepatocellular carcinoma [27], oral tongue squamous cell carcinoma [29] and gastric cancer [30]. This may be due to that the domain of FNIII was involved in cell adhesion [31,32], which can promote cell proliferation and migration, especially in the development of tumor [33].…”
Section: Discussionmentioning
confidence: 99%
“…Fibronectin type III domain containing 3B (FNDC3B, also FAD104), a member of FNDC3 family, was previously identified as a modulator of osteoblast and adipocyte differentiation. 5,6 The fibronectin type III domain is a main structural component of FNDC3B, along with the transmembrane region and proline-rich region. 7 As the fibronectin type III domain has the ability to combine with various proteins, FNDC3B plays an important role in multiple cell processes, including cell adhesion, proliferation and growth signaling.…”
Section: Introductionmentioning
confidence: 99%